Effect of recycling on the time- and temperature-dependent mechanical properties of PP/MWCNT composite liner materials - Attila Bata; Péter Gerse; Krisztián Kun; Emese Slezák; Ferenc Ronkay (Results in Engineering)
The application of multi-walled carbon nanotubes (MWCNTs) provides a promising solution to increase the mechanical properties of polypropylene (PP), even after recycling. These preliminary findings reveal that recycled PP/MWCNT composites can provide structural integrity, making them suitable for high-performance applications like hydrogen storage. The improved Young's modulus and reduced creep tendency in recycled PP/MWCNT nanocomposites indicate that these materials can be used in Type IV hydrogen storage vessels, where long-term durability and resistance to mechanical stress are fundamental. In this study twin-screw extrusion was used to prepare the nanocomposites and their recyclates with 0.3, 0.5, and 1 w/w% MWCNT content, followed by injection molding to produce test specimens. Tensile and dynamic mechanical analysis (DMA) tests revealed that Young's and storage modulus of the recyclates increased, while elongation at break decreased compared to the base material due to the mechanical properties and stiffness of MWCNT. The glass transition temperature of the recycled composites minimally declined, and the Cole-Cole curves broadened yet retained the same character as the unfilled base material, indicating composite homogeneity. A novel method was applied in physical-mechanical measurements to evaluate MWCNT efficiency, predicting its effect across the temperature range typical for hydrogen-powered vehicles and determining the optimal filler content for maximum reinforcement efficiency. Creep tests, simulating constant pressure on the liner layer of a type IV tank, showed that PP/MWCNT recyclates exhibited a lower creep tendency than the unfilled base material, attributed to the stress-distributing effect of the filler.